A Juridical Policy For Crime Of Murder Committed By A Child In The Framework Of Child Justice Protection - Mhd. Sanip Heri Sinaga; Firman Halawa; Yasmirah Mandasari Saragih (Sean Institute, 2024)
A recently, more and more criminal acts have been committed by children and minors as defendants in trials, to guarantee and protect children and their rights so that they can live, grow, develop and adapt optimally in accordance with human dignity, and receive protection. from violence and discrimination. As for children who are in conflict with the law (children who commit criminal acts) must be processed according to the provisions of the applicable law so that the supremacy of the law is achieved. The application of criminal law to criminal acts of premeditated and non-premeditated murder which cause death committed by children. The application of criminal provisions in this case is in accordance with the legal facts, including witness statements, expert statements, and the defendant's statement and the defendant is considered physically and mentally healthy, no can be mentally disturbed so that they are unable to take responsibility for their actions. This paper describes the criminal responsibility policy in the context of legal protection for children, namely providing punishment and action for children who commit criminal acts, as per the provisions contained in the Law on the Juvenile Criminal Justice System.